Computer therapy for the anxiety and depressive disorders is effective, acceptable and practical health care: a meta-analysis - Andrews, G.; Cuijpers, P.; Craske, M.; McEvoy, Peter; Titov, N. (Public Library of Science, 2010)
Background: Depression and anxiety disorders are common and treatable with cognitive behavior therapy (CBT), but access to this therapy is limited.Objective: Review evidence that computerized CBT for the anxiety and depressive disorders is acceptable to patients and effective in the short and longer term.Method: Systematic reviews and data bases were searched for randomized controlled trials of computerized cognitive behavior therapy versus a treatment or control condition in people who met diagnostic criteria for major depression, panic disorder, social phobia or generalized anxiety disorder. Number randomized, superiority of treatment versus control (Hedges g) on primary outcome measure, risk of bias, length of follow up, patient adherence and satisfaction were extracted.Principal Findings: 22 studies of comparisons with a control group were identified. The mean effect size superiority was 0.88 (NNT 2.13), and the benefit was evident across all four disorders. Improvement from computerized CBT was maintained for a median of 26 weeks follow-up. Acceptability, as indicated by adherence and satisfaction, was good. Research probity was good and bias risk low. Effect sizes were non-significantly higher in comparisons with waitlist than with active treatment control conditions. Five studies comparing computerized CBT with traditional face-to-face CBT were identified, and both modes of treatment appeared equally beneficial. Conclusions: Computerized CBT for anxiety and depressive disorders, especially via the internet, has the capacity to provide effective acceptable and practical health care for those who might otherwise remain untreated.